Ekwiwalencja przekładu w kontekście oceny wiarygodności zeznań świadka - Katarzyna Liber-Kwiecińska (Ksiegarnia Akademicka Publishing, 2019)
Equivalence of Written Translation in the Context of the Assessment of the Credibility of Witness Testimony This article presents a study on the equivalence of written translation in the context of the assessment of the credibility of witness testimony. Part one examines psychological criteria for assessing the credibility of testimony and linguistic indicators of deception that formed the theoretical basis of the study. Translations gathered during the study were analyzed linguistically and compared with original in order to categorize the errors and mistakes made by translators before and after learning the criteria of statements credibility assessment in training. The article also presents a comparative analysis of the assessments made by expert judges with regard to both the original testimonies and the translations thereof. The results of the statistical analysis showed that there are certain differences in the assessment of an original and its translation, and knowledge of the criteria for determining the credibility of a witness’s testimony has a positive impact on translation equivalence.